IN VITRO SOMATIC EMBRYOGENESIS IN ERYNGIUM FOETIDUM L. – A MEDICINAL HERB. - M.S.SUDARSHANA,; AKSHATHA, B.H,,; MAHENDRA, C,; GURU, C, (International Journal of Pharma and Bio Sciences, 2014)
High frequency somatic embryogenesis and plant regeneration was achieved on calli developed from internodal and flower buds of E. foetidum. The explants were cultured on Murashige and Skoog medium supplemented with different concentrations and combinations of BA and IAA. The nodal explants produced multiple adventitious shoots while the internodal and flower buds induced callus, from which multiple shoot buds originated. Both direct and indirect shoots elongated within 4-6 weeks of culture. The well- organized shoots were individually separated and transferred to half strength MS liquid medium containing NAA or IAA at different concentrations. Rhizogenesis was observed within two weeks of transfer. They are transferred to polycups containing vermiculite for acclimatization and finally transplanted to soil. Histology of embryogenic calli revealed the presence of various types of embryoid and shoot buds both in the internodal and inflorescence calli. Upto fifty-five percent of the plants survived under field conditions.